Greenhouse Gas Emissions from Cotton Field under Different Irrigation Methods and Fertilization Regimes in Arid Northwestern China. (16th July 2014) - Wu, Jie; Guo, Wei; Feng, Jinfei; Li, Lanhai; Yang, Haishui; Wang, Xiaohua; Bian, Xinmin
Abstract : Drip irrigation is broadly extended in order to save water in the arid cotton production region of China. Biochar is thought to be a useful soil amendment to reduce greenhouse gas (GHG) emissions. Here, a field study was conducted to compare the emissions of nitrous oxide (N2 O) and methane (CH4 ) under different irrigation methods (drip irrigation (D) and furrow irrigation (F)) and fertilization regimes (conventional fertilization (C) and conventional fertilization + biochar (B)) during the cotton growth season. The accumulated N2 O emissions were significantly lower with FB, DC, and DB than with FC by 28.8%, 36.1%, and 37.6%, while accumulated CH4 uptake was 264.5%, 226.7%, and 154.2% higher with DC, DB, and FC than that with FB, respectively. Irrigation methods showed a significant effect on total global warming potential (GWP) and yield-scaled GWP (P < 0.01 ). DC and DB showed higher cotton yield, water use efficiency (WUE), and lower yield-scaled GWP, as compared with FC and FB. This suggests that in northwestern China mulched-drip irrigation should be a better approach to increase cotton yield with depressed GHG. In addition, biochar addition increased CH4 emissions while it decreasedN 2 O emissions.